Komunikasi Positif Dalam Pengasuhan Anak Usia Dini - Isna Siskawati (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of this study is to recommend readers to change their parenting communication style from traditional communication style to positive communication. Qualitative research methods with a library study approach. Data collection techniques with documentation. Data reduction processing techniques, presentation and conclusion. The results of the study show: positive communication steps in early childhood care are obtained: (1) leaving traditional communication styles: by changing the message of communication to children. (2) use the message